ASSISTANCE TO THE NATURAL BATHS TOURISM MANAGEMENT KARANG ANYAR KARANG REJO VILLAGE SIMALUNGUN REGENCY - Riza, Ade Ros; Valianto, Budi; Saputra, Hendra; Marpaung, Deni Rahman; Fadli, Zen; Ratno, Puji (Universitas Negeri Medan, 2025)
Karang Anyar bathing attraction is a tourist location managed by the community of Karang Rejo Village, Gunung Maligas District, Simalungun Regency. This tourist attraction is managed independently by a community of 10 people. Partners market their tourist objects still in a conventional way. The main problems faced by partners are, in the management of this tourist attraction, financial management is carried out conventionally, the cleanliness of tourist sites that have not been well organized. Marketing of tourist sites is still done in a conventional way. The cleanliness of the tourist attraction location is getting better, 90% of visitors are satisfied with the cleanliness of the tourist attraction. 2. The existence of a cash book that is used in recording income and expenses of tourist attractions. 3. The existence of social media accounts on Facebook, Instagram, and TikTok which are used for marketing Karang Anyar natural bathing objects. The direct impact of this activity is the increase in the number of visitors by 45% from the average previous visit.